Visualizing climate targets: mapping the 93 funded E.U. Erasmus+ projects versus SDGs and horizon missions targets<subtitle>The case of the Knowledge Alliances program versus SDG13 and HM2 & HM5</subtitle> - Mennatullah Hendawy (Journal of Maps)
This study investigates the 93 awarded projects from the Erasmus+ Knowledge Alliances (KA) program between 2014 and 2018 from the perspective of their contribution to the climate-related UN Sustainable Development Goals (SDGs) – SDG13: Climate Action and the climate-related European Commission’s Horizon Missions (HMs) – HM2: Climate-neutral and Smart Cities and HM5: Climate Change Adaptation and Societal Transformation. It aims to investigate if the KA projects have advanced the progress toward achieving climate targets. KA projects address sustainability transitions in Europe. After indexing the projects, a three-step system for analysis was adopted. First, a content analysis of the description written about each project in the advertised booklet. Then, via human screening, the projects were identifed in relation to the UN SDGs and HMS and then identified the projects that have climate-related targets. Afterward, these findings were visualized to associate the SDGs and HMs with the geographic location of the projects. This study contributes to the understanding of the KA-awarded projects in relation to the climate-related targets. The studu shows that the majority of KA projects do not have climate-related targets although they claim to foster transformative learning in sustainability education practices. This demonstration may help evaluate the efficacy of EU programs and funding lines at large, despite the EU's climate neutrality policies. It also raises questions about the effectiveness and on-ground fund allocation concerning the climate crisis.